Health-Related Quality of Life and Daily Physical Activity Level in Patients with COPD- a Cluster Analysis - Carvalho da Silva, Marcela Maria; Arcuri, Juliano Ferreira; Pott, Henrique; Sentanin, Anna Claudia; Zorrer Franco, Francisco José Barbosa; da Costa Trondoli, Luiz Henrique Pessôa; Di Lorenzo, Valéria Amorim Pires (Chronic obstructive pulmonary disease, 2022)
Patients with chronic obstructive pulmonary disease (COPD) may have a limited level of physical activity in daily life (PADL) and health-related quality of life (HRQOL). The interrelationships of these variables should be measure by cluster analysis to characterize this population and enable rehabilitation programs to target each patient profile identified. This study investigates different phenotypes in COPD according to PADL and HRQOL. A cross-sectional study with cluster analysis was done, in which 76 people with COPD were submitted to measurements to characterize the sample on first day, followed by used of physical activity monitor, which was worn for 7 days. After 7 days, the six-minute walk test (6MWT) and HRQOL questionnaires were applied (St. George's Respiratory Questionnaire). The main results: three phenotypes were identified (A, B and C), with phenotype A who exhibited an inactive physical activity level and HRQOL scores above the value deemed satisfactory, phenotype B those with active physical activity level and poor HRQOL scores, and phenotype C subjects with inactive physical activity level and HRQOL scores but the value is close to cutoff point. To conclude, three phenotypes were found, with one indicating disproportionality between PADL and HRQOL.